Public Response Analysis toward Poverty Reduction Program in Indonesia 2014-2018 through Twitter Data - Mohammad Ilham Nur Rohman; Siti Mariyah (Telkom University, 2019)
Poverty reduction is the main priority of national development, it aims to encourage the improvement of the welfare of the poor in order to enjoy increasingly quality economic growth . But, every government program really needs an evaluation and how the response from the public. Social media monitoring can be used to understand and provide real-time feedback about policy reform. Therefore, government are expected to consider using similar technology in the current evaluation and operational framework. So they need tools to analyze the public response to poverty reduction programs in Indonesia by using Big Data through twitter data. With this research, it is expected that the public response from social media twitter can be a critique and suggestion for the government in establishing and implementing future poverty reduction policies. This research conducted to use twitter data on poverty reduction policies in Indonesia, such as: “Bedah Kemiskinan Rakyat Sejahtera(BEKERJA)” Program, “Padat Karya Tunai” Program, and “Program Keluarga Harapan”. Data are sourced from all community tweets related to the programs. There are analyzed using the text mining method. The results of this study indicate that in general the public response received and supported three poverty reduction programs in Indonesia for the 2014-2018 period. So public response can be used as an evaluation and input to the government.